Improved Upland Cotton Germplasm for Multiple Fiber Traits Mediated by Transferring and Pyramiding Novel Alleles From Ethyl Methanesulfonate-Generated Mutant Lines Into Elite Genotypes - Patel, Jinesh D.; Khanal, Sameer; Chandnani, Rahul; Adhikari, Jeevan; Brown, Nino; Chee, Peng W.; Jones, Don C.; Paterson, Andrew H. (Frontiers in Plant Science, 2022)
EMS-mutagenesis offers important advantages for improving crops such as cotton with limited diversity in elite gene pools. EMS-induced point mutations are less frequently associated with deleterious traits than alleles from wild or exotic germplasm. From 157 mutant lines that have significantly improved fiber properties, we focused on nine here. A total of eight populations were developed by crossing mutant lines in different combinations into GA230 (GA2004230) background. Multiple lines in each population were significantly improved for the fiber trait that distinguished the donor parent(s), demonstrating that an elite breeding line (GA230) could be improved for fiber qualities using the mutant lines. Genotypes improved for multiple fiber traits of interest suggest that allele pyramiding is possible. Compared to mid parent values, individual progeny in the population conferred fiber quality improvements of as much as 31.7% (in Pop. O) for micronaire, 16.1% (in Pop. P) for length, 22.4% (in Pop. K) for strength, 4.1% (in Pop. Q) for uniformity, 45.8% (in Pop. N) for elongation and 13.9% (in Pop. O) for lint percent. While further testing for stability of the phenotype and estimation of yield potential is necessary, mutation breeding shows promise as an approach to reduce the problem of the genetic bottleneck of upland cotton. The populations developed here may also contribute to identifying candidate genes and causal mutations for fiber quality improvement.